Informasi Dalam Perspektif Islam - Solehudin, Much (Jurnal Teknologi dan Bisnis, 2020)
Information is a communication tool that is always needed by humans every day. Especially as material interaction between one person with another. The author presents an overview of Information in Islamic Perspectives. With the formulation of the problem of how information is viewed from the perspective (Perspective) of Islam. This type of research is to use a literature study where the author collects some data then the writer explores the data in accordance with the discussion of information in an Islamic perspective. The results of this study that Information in Islamic Perspectives have been listed in the Qur'an as well as the characteristics of the information to be conveyed should a) Qashash / Naba al Haq, in which there are characteristics in providing information such as: Information that contains the truth, does not hide the truth , can resolve differences of opinion, edify, not follow subjective desires, bring good news. b) A'mar ma'ruf nahyi munkar means not inviting goodness and preventing evil. c) Wisdom, meaning that every information contains benefits that can be received by the recipient of the information. d) Tabayyun, to prevent prejudice, the recipient of the information is taught to clarify it first when getting information. e) Mauizhah Hasanah, The information conveyed should contain a good example. f) Layyin, Avoid harsh words and use gentle speech and language, so that the recipient of the information does not feel offended. Islam has determined the rules that need to be considered by a Muslim who has a profession as a seeker and messenger of information. The rules determined by Islam through the Qur'an and al-Hadith about ethics that need special attention by a seeker and conveyor of information are related to the form and type of information that will be conveyed both by means and technique.